FAKTOR PENENTU KEPUTUSAN PENGAMBILAN KREDIT DAN PENGARUHNYA TERHADAP KINERJA USAHATANI TEBU DI JAWA TIMUR - Nur Rizky Alfiani; Herawati Herawati; Harianto Harianto (Jurnal Penelitian Pertanian Terapan, 2025)
Sugarcane is one of Indonesia's leading plantation commodities. East Java, with the highest contribution to sugarcane plantations in Indonesia, is experiencing a downward trend in production and land area. Farmers experience a problem with limited capital. Credit is a solution to strengthen farmers' capital structures. However, credit uptake is still not optimal given the available ceiling. This study aims to analyze the factors that influence farmers' decisions to take credit and their effect on the performance of sugarcane farming in East Java. The data used is secondary data from the 2014 Plantation Business Household Survey. The respondents consisted of 1.040 credit farmers and 3.587 non-credit farmers. The methods used were logistic regression and Propensity Score Matching (PSM). The findings demonstrated that factors such as age, land size, seed varieties, cooperative membership, farmer group membership, partnership involvement, and association participation had an impact on farmers' credit decisions. Higher total production, revenue, costs, and income compared to non-credit indicate that credit has a positive impact on farm performance.